Amanat dalam Crita-Crita Lucu Basa Jawa ‘Kok Rena-Rena’ Karya Gayuh R. Saputro (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2023)
This qualitative research aimed to describe the message within the collection of Javanese Funny Stories ‘Kok Rena-Rena’ by Gayuh R. Saputro. This research used content analysis with data reduction, data presentation, verification, and conclusion drawing steps. The results of the analysis show that there are twelve messages that can be learned from these short stories, as follows: (1) actions that are considered trivial can harm other people; (2) bad luck can come to anyone, anytime, and anywhere; (3) it is better to be honest than unlucky; (4) there is no rattan, the root becomes/every little helps; (5) prohibition rules can bring disaster; (6) anything in excess is not good; (7) being annoyance with other people can be self-defeating; (8) carelessness in acting can result in embarrassment; (9) when speaking, it must be detailed and clear so as not to cause misunderstandings; (10) being more careful after having a bad experience; (11) learning regardless of age, social status, and prestige; (12) someone needs to have solutions to solve problems.
Keywords: Massage; Javanese Funny Stories; Kok Rena-Rena